PENGARUH PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT.KARYA AGUNG PALEMBANG. - Firdaus Sianipar (Fakultas Ekonomi Universitas Tridinanti Palembang, 2013)
ABSTRACTEffect of monitoring the performance of employees at PT. Karya Agung of Palembang study was conducted to determine the effect of variable monitoring the performance of employees at PT. Karya Agung of Palembang, while the samples used in this study is the entire population of employees atÃ‚Â PT. Karya AgungÃ‚Â of Palembang as many as 30 people. The research method used is the data collection techniques by using an interview, kuesiner and literature. Analissis hypothesis testing using simple linear regression using the SPSS test tools,to determine the relationship efesiansi the supervision of the t test at the 95% confidence level or a = 0.05% results from this research that the value of R Sguare or coefficient of determination of 0.135 indicating that 13.50% variable performance can be explained by oversight, while the remaining 86.5% is explained by the variables that were not studied that discipline, job design, compensation, work climate, and others. The Ã‚Â Ã‚Â Ã‚Â results Ã‚Â Ã‚Â showedÃ‚Â Ã‚Â Ã‚Â that Ã‚Â Ã‚Â control Ã‚Â Ã‚Â relationship with the performance of 36,7% means that the relationship is very weak.Ã‚Â Key works: monitoring, performance, leadershipÃ‚Â